The Comprehensive Systematic Review of Traumatic Brain Injury and Visual Disorders - Cintya Ristimawarni; Kaharuddin Yunus; Nazza Rizky Ramdhagama (International Medical Journal Corp. Ltd, 2025)
Background: Traumatic brain injury (TBI) is a leading cause of death and disability globally, affecting predominantly children, young people, and the elderly. Complications include concussions, focal injuries, and diffuse damage. Visual impairments caused by traumatic brain injury can have an influence on quality of life and functional independence. Understanding the relationship between TBI and visual abnormalities is critical for creating effective diagnostic tools and treatment plans. Methods: This systematic review followed PRISMA 2020 guidelines, concentrating solely on full-text articles published in English from 2014 to 2024. Editorials and review articles lacking a DOI were excluded to ensure the use of high-quality sources. A literature review was performed using reputable databases such as ScienceDirect, PubMed, and SagePub to identify pertinent studies. Result: The preliminary database search revealed more than 200 relevant papers on the subject. Following a comprehensive three-stage screening process, eight studies were selected that met the specified inclusion criteria for in-depth analysis. The research were subjected to rigorous critical assessment, enabling an in-depth analysis of traumatic brain injury and visual disorders. This focused approach ensured that the analysis employed strong evidence closely linked with the study's objectives. Conclusion: TBI patients often experience visual dysfunctions, affecting their outcomes. The severity and type of injury significantly influence these issues. Comprehensive eye examinations are crucial for detecting subtle impairments, and long-term monitoring and rehabilitation strategies are essential for improved patient care.